(untitled) (Research, Society and Development, 2021)
This article consists of a narrative review of the literature on public health and social policies for children in Brazil that contributed to the reduction of the Child and Under-five child Mortality Rate. Search was carried out in Medline, Lilacs, PAHO databases, in government documents and on Google Scholar, covering the period from 1973 to 2015. Data collection occurred between November 2018 and June 2019 from the themes child and under-five child mortality in Brazil, including in the review all full-text articles, government documents and laws that directly or indirectly addressed child and/or under-five child mortality published in the Portuguese language. The numerous strategies, programs and public health and social policies developed over the years were essential for achieving reductions in child and under-five child mortality rates in Brazil. The advances made are cause for celebration, however the current scenario remains a challenge in terms of maintaining the reduction of these rates.